Who owns outer space? : international law, astrophysics and the sustainable development of space / Michael Byers, University of British Columbia, Vancouver; Aaron Boley, University of British Columbia, Vancouver. - Byers, Michael, 1966-; Boley, Aaron (Cambridge studies in international and comparative law ;, 2023)
From Space debris to asteroid strikes to anti-satellite weapons, humanity's rapid expansion into Space raises major environmental, safety, and security challenges. In this book, Michael Byers and Aaron Boley, an international lawyer and an astrophysicist, identify and interrogate these challenges and propose actionable solutions. They explore essential questions from, 'How do we ensure all of humanity benefits from the development of Space, and not just the world's richest people?' to 'Is it possible to avoid war in Space?' Byers and Boley explain the essential aspects of Space science, international law, and global governance in a fully transdisciplinary and highly accessible way. Addressing the latest and emerging developments in Space, they equip readers with the knowledge and tools to engage in current and critically important legal, policy, and scientific debates concerning the future development of Space. This title is also available as Open Access on Cambridge Core.